Characterization of the rainbow trout (Oncorhynchus mykiss) breeding in the province of Chincheros, Apurimac, Peru - Zárate M., Ivar (2018)
The purpose of the study was to characterize the production of rainbow trout (Oncorhynchus mykiss) in the province of Chincheros, Apurímac. Interviews were done to 85% of the producers (n=21) through a survey between November and December 2017. In general, 85.7% of the respondents were over 40 years old, where 42.9% had complete secondary education. The two main activities developed by the producers were agriculture (38.0%) and trout farming (33.3%). More than 50% produced more than three tons of trout per year. The pools were constructed with soil and cement (38.0%), the water supply was mainly from springs (85.7%). About half of the respondents had potable water and electricity services in their productive centres. Most purchase fingerlings as seed (85.7%), which are mostly bred for 7 and 8 months. Most episodes of mortality occur in the summer season (85%) and are attributed to changes in temperature and oxygen descent. Moreover, 75% of the producers use balanced food and the majority ration it three times a day. The weight of sale was between 200 to 250 g, which are sold mainly as whole trout at a price of between 15 and 25 soles per kilogram (1 US$=S/. 3.25).